PROTOTYPING METHOD IMPLEMENTATION IN HEALTH LABORATORY SERVICE INFORMATION SYSTEM AT LAMPUNG PROVINCE - Saputra, Gustrio; Suhelmi, Ahmat; Nizamiyati, Nizamiyati; Puspitasari, Ida Ayu; Howards, Williams (Universitas Islam Negeri Raden Intan Lampung, 2022)
UPTD Lampung Province Health Laboratory Center is a health laboratory examination service unit including Complete Urine Laboratory, Blood Chemistry, Microbiology, Body Fluid Analysis, Culture and Identification, Hematology, Health Chemistry, Immunology / Serology and medical check-up services. With the implementation of the application of the prototyping method in the health laboratory service information system, it can minimize costs and operational time, of course, it can be accessed anywhere and anytime. This laboratory service information system was built using PHP, MySQL and bootstrap while the development method was Prototype. The laboratory service information system at the Mobile-Based UPTD Health Laboratory Center for Lampung Province can speed up the administrative service process in terms of registration of examinations according to the type of patient examination, lab examination results, payments and patient consultations which can be done online without having to come.